Exploring the Mediating Role of Brand Image in Linking Word of Mouth and Digital Marketing Decisions - Nugroho, Anton; Fadhilah, Muinah; Lukitaningsih, Ambar (Economics, Business, Accounting & Society Review, 2025)
The construction service industry in Indonesia plays a crucial role in national economic growth, contributing significantly through major infrastructure projects. However, the increasing competition among construction service companies has made it essential for businesses to adopt effective marketing and reputation-building strategies. This study aims to analyse the effect of Word of Mouth (WOM) and digital marketing on the decision to use contractor services, with brand image as a mediating variable, especially at CV. Adicitra Karya in Yogyakarta. This study used a survey of 20 consumers of CV Adicitra Karya, with data collected using a structured questionnaire with a Likert Scale. Data analysis was conducted with Partial Least Squares (PLS) to test the validity, measurement model, and structural model. The results show that WOM has a significant effect on brand image, which in turn affects service utilisation decisions. Digital marketing does not have a significant effect on service utilisation decisions, and its effect on brand image is also limited. This research is useful for businesses in the construction industry, digital marketing, and service-based industries. This research provides insights into how WOM and digital marketing influence consumer decisions, especially in service industries such as construction. This research enriches knowledge by exploring the interactive relationship between WOM, digital marketing, and brand image in the context of construction services. This research provides a unique perspective on how WOM can influence consumer decisions through brand image, especially in a sector that relies heavily on trust and reputation.